2003
DOI: 10.1016/s1097-2765(03)00145-x
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of Skp1-Bub1 Interaction for Kinetochore-Mediated Activation of the Spindle Checkpoint

Abstract: The spindle checkpoint transiently prevents cell cycle progression of cells that have incurred errors or failed to complete steps during mitosis, including those involving kinetochore function. The molecular nature of the primary signal transmitted from defective kinetochores and how it is detected by the spindle checkpoint are unknown. We report biochemical evidence that Bub1, a component of the spindle checkpoint, associates with centromere (CEN) DNA via Skp1, a core kinetochore component in budding yeast. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 53 publications
2
38
0
Order By: Relevance
“…Knockdown of RB1 and SKP1A can increase G2 populations, 47,48 and CDKN1B is a validated target. 49,50 We note that in different cell lines mir-222 can induce either an S-phase or G1-accumulation.…”
Section: Regulation Of the Mir-424-503 Polycistronmentioning
confidence: 99%
“…Knockdown of RB1 and SKP1A can increase G2 populations, 47,48 and CDKN1B is a validated target. 49,50 We note that in different cell lines mir-222 can induce either an S-phase or G1-accumulation.…”
Section: Regulation Of the Mir-424-503 Polycistronmentioning
confidence: 99%
“…Recent studies have begun to shed light on this baffling question in the spindle checkpoint field. Recently, the yeast Skp1 protein has been identified as a Bub1-binding protein in a yeast two-hybrid screen (Kitagawa et al, 2003). The physical interaction between the two proteins is direct, as demonstrated by in vitro binding assays using recombinant proteins (Kitagawa et al, 2003).…”
Section: Recruitment Of Bub1 In Yeastmentioning
confidence: 99%
“…Recently, the yeast Skp1 protein has been identified as a Bub1-binding protein in a yeast two-hybrid screen (Kitagawa et al, 2003). The physical interaction between the two proteins is direct, as demonstrated by in vitro binding assays using recombinant proteins (Kitagawa et al, 2003). Furthermore, Skp1 was shown to be required for the recruitment of Bub1 to kinetochores in yeast (Kitagawa et al, 2003).…”
Section: Recruitment Of Bub1 In Yeastmentioning
confidence: 99%
“…In both cases, F-box proteins are degraded after ubiquitin modification, a process proposed to be important for the formation of new SCF complexes (Zhou and Howley, 1998). The turnover of Ctf13p may also contribute to the ability to create new CBF3 complexes, a process that may be linked to maintenance of the spindle checkpoint (Kitagawa et al, 2003). Interestingly, it has been reported that Skp1p is required for the turnover of Rcy1p, a protein involved in the recycling of SNARE complexes, independent of its role in SCF (Galan et al, 2001); this result and our observations concerning the stability of CBF3 in skp1-3 cells raises the possibility that Skp1p contributes to the turnover of proteins independent of ubiquitin-mediated degradation.…”
Section: Mechanism Of Skp1p-sgt1p Actionmentioning
confidence: 99%
“…Instead, it acts to nucleate and organize a large number of outer kinetochore complexes (Basu et al, 1999;Ortiz et al, 1999;Jones et al, 2001;Janke et al, 2002;Li et al, 2002;Measday et al, 2002). Although its interaction with microtubules is indirect, it has been recently shown that Skp1p directly interacts with the spindle checkpoint protein Bub1p, suggesting that CBF3 may be intimately connected to the regulatory machinery that ensures proper kinetochore-microtubule attachment has occurred before the onset of anaphase (Kitagawa et al, 2003).…”
Section: Introductionmentioning
confidence: 99%